The myosin step size: measurement of the unit displacement per ATP hydrolyzed in an in vitro assay. - Toyoshima, Y Y (1990)
Chemomechanical coupling in muscle contraction may be due to "swinging crossbridges," such that a change in the angle at which the myosin head binds to the actin filament is tightly coupled to release of products of ATP hydrolysis. This model would limit the step size, the unit displacement of actin produced by a single ATP hydrolysis, to less than twice the chord length of the myosin head. Recent measurements have found the step size to be significantly larger than this geometric limit, bringing into question any direct correspondence between the crossbridge and ATP-hydrolysis cycles. We have measured the rate of ATP hydrolysis due to actin sliding movement in an in vitro motility assay consisting of purified actin and purified myosin. We have calculated an apparent myosin step size well within the geometric limit set by the size of the myosin head. These data are consistent with tight coupling between myosin crossbridge movement and ATP hydrolysis.